Between Fear and Faith (Examining the 'Marriage Is Scary' Phenomenon through Maqāshid al-Sharī'ah and Institutional Response in Medan, Indonesia) - Faishal; Ibnu R Siddik Turnip; Iwan (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study examines the Marriage is Scary phenomenon among young generations in Medan City, characterized by increasing fear of marriage driven by economic concerns, family trauma, and social media influence, and analyzes it from the perspective of Islamic Family Law. Using a qualitative field research approach through interviews, observations, and documentation involving young adults and officials at the Office of Religious Affairs (KUA) Medan, the study reveals that this trend reflects low legal awareness and a weakened understanding of Islamic values related to marriage, thereby contradicting the maqāshid al-sharī‘ah, particularly ḥifẓ al-nasl and ḥifẓ al-‘ird. Although KUA Medan has responded through premarital counseling and digital education initiatives, their effectiveness remains limited due to low youth participation and a lack of innovative material. The study concludes that strengthening legal awareness, applying progressive legal approaches, and internalizing maqāshid-oriented education are essential to shaping positive perceptions of marriage among young Muslims.